Non-invasive methods to assess muscle function in dogs: A scoping review - Dahl, Kathrine Højte; Zebis, Mette Kreutzfeldt; Vitger, Anne Désiré; Miles, James Edward; Alkjær, Tine (Frontiers in Veterinary Science, 2023)
Skeletal muscle function can be affected by multiple disorders in dogs of which cranial cruciate ligament rupture or disease (CCLD) is one of the most common. Despite the significance of this condition only sparse research exists regarding assessment of muscle function in dogs. This scoping review aimed to identify the non-invasive methods for canine muscle function assessments that have been reported in the literature in the past ten years. A systematic literature search was conducted 1st March 2022 across six databases. After screening, 139 studies were considered eligible for inclusion. Among the included studies, 18 different muscle function assessment categories were identified, and the most frequently reported disease state was CCLD. We included an attempt to elucidate the clinical applicability of the 18 reported methods, as experts were asked to subjectively assess the methods for their clinical relevance as well as their practical applicability in dogs with CCLD.